Digitalisasi Administrasi Desa Melalui Pelatihan Pengelolaan Data Berbasis Sistem Informasi - Willy Prihartono; Yudhistira Arie Wijaya; Arya Hadi Wicaksana; Astri Amelia (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Digitalization of village administration is a solution to improve the efficiency and transparency of data management at the village level. This transformation allows village governments to manage information more systematically, reduce administrative errors, and improve services to the community. This research focuses on training on data management based on information systems implemented in villages, to provide village officials with an understanding of the importance of digitization in governance. The method used in this training includes a participatory approach with a combination of theory and hands-on practice in the use of information systems. The results of the training showed that the majority of participants experienced improved understanding and skills in operating digital systems for village administration. The implementation of digitalization also contributed to improving transparency, data accuracy, and accelerating the process of administrative services to village communities. The challenges faced include limited technological infrastructure, resistance to change, and the need for continuous assistance. Therefore, policies that support the development of human resource capacity and investment in information technology infrastructure in villages are needed. Thus, the digitization of village administration can run optimally and sustainably to support technology-based village development.